A Guideline of Creating Shared Value in Business and Industrial Sector - Vongmahasetha, Thanakit; Shoommuangpak, Porntip (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2020)
The research aims to study the guideline for structural equation model development on creating shared value management of business and industrial sector listed in the Stock Exchange of Thailand. The sample of the study was 500 entrepreneurs in business and industrial sector listed in the Stock Exchange of Thailand with experiences in creating shared value management. The instrument was the questionnaire, which was related to creating shared value management of business and industrial sector listed in the Stock Exchange of Thailand. The analysis of the data was the structural equation model. The result found that the elements of structural equation model on creating shared value management of business and industrial sector listed in the Stock Exchange of Thailand were composed of 1 Exogenous Latent Variable, which is the Community Participation as well as 4 Endogenous Latent Variables, which are Resource Sufficiency, Knowledge Management, Creative Marketing, and Innovation. The 5 elements of the guideline for development on creating shared value management are fit for empirical data with the p value of Chi-Square = 0.167 / CMIN/DF = 1.112 / GFI = 0.967 / RMSEA = 0.015 at the significance level of 0.05. The guideline for creating shared value management of business and industrial sector listed in the Stock Exchange of Thailand 0.84, respectively. The result of the analysis formulates good value for creating shared value management of business and industrial sector listed in the Stock Exchange of Thailand as well as confirms the sustainability of the business. has a positive effect with the path coefficient indicates the direct effect of 0.42 0.81 0.99 0.55 and